Pedagogical-Didactic Strategy to promote critical reading - Pinchao Benavides, Luis (2024)
This article gathers the experience of classroom research called: the textual macrostructure as a pedagogical-didactic strategy to promote critical reading in undergraduate students. The project undertaken in January 2013 and completed in December 2014, assumes one of the problems experienced daily by students in their academic development: the limited ability to live in critical reading. This is an action research in education that uses a critical reading sheet, designed to identify semantic macrostructures in argumentative-descriptive texts. This research activity allowed us to observe step by step the way in which students explore and display other forms of reading, other than literal. The study helped validate the critical reading sheet as a pedagogical-didactic strategy that favors high-level reading.